Chinese Regional Differences and Commonality in Field-Independence and Field-Dependence: An Implicit Biculturalism Model - Liu, Wenli; Dai, Zhaobin; Yang, Shiwei; Ng, Sik Hong; Zhang, Xiaocui; Peng, Shenli (Frontiers in Psychology, 2022)
Comparative studies of cultural-cognitive systems in China have stressed differences between northern and southern regions, with less attention paid to inter-regional commonality. This study proposes an implicit biculturalism model to rectify the diversity bias. The model posits that Chinese in both regions have internalized the same two cultural-cognitive systems but have organized them differently. For northerners, the individualist/analytical system (indicated by field-independence) is more dominant and chronically accessible than the collectivist/holistic system (indicated by field-dependence); for southerners the hierarchical order is reversed. The more dominant system would normally manifest in everyday life as the default situation, but the less dominant system could be activated through cultural priming. Both field-independent northerners (N = 46) and field-dependent southerners (N = 46) were assigned randomly into individualistic and collectivistic priming conditions and then tested with the Embedded Figure Test (EFT). The results indicated field-independent northern Chinese changed their EFT performance to be field-dependent under collectivism priming, and field-dependent southern Chinese changed their EFT performance in the field-independent direction, albeit to a less extent, under individualism priming. Generally, these results supported the implicit biculturalism model, which provides a more nuanced understanding of the question of “Who are the Chinese in Chinese psychology?”